(untitled) (SCIÉNDO INGENIUM, 2021)
The purpose of the research was to determine the effectiveness of a Counseling Program on cures for the prevention of body falls, for this purpose the identification of the level of knowledge about body fall prevention care of the family caregivers of the adults was made. -sores; Likewise, the level of overload of the family caregivers of older adults was determined before and after the application of the Counseling Program. The study was approached as a quantitative, quasi-experimental research with a single group, with a sample universe of 42 family caregivers of the older adult of the Center for the Elderly - Es-Salud-Trujillo and with a representative sample of 30 caregivers. categorization yields a high level of knowledge greater than or equal to 8 points; and a slight overload level of 47% to 55% and an intense overload of greater than or equal to 56%. It is concluded that the program of counseling on prevention of corporal falls was effective to increase the level of knowledge and reduce the level of overload of family caregivers.